Effect of carnichrome® on growth performance of weanling pigs in a commercial environment - Frantz, N.Z.; Woodworth, J.C.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A 43-day growth study with a total of 384 weanling pigs (14 ± 2 d of age) was conducted to evaluate the effects of Carnichrome®, a combination of L-carnitine and chromium picolinate, on growth performance of weanling pigs. Secondary objectives were to compare pigs fed diets with or without a feed-grade medication, evaluate any interactive effects between Carnichrome and medication, and identify any carryover effect once medication was withdrawn from the diet. Experimental diets were arranged in a 2 × 3 factorial to compare the main effects of medication (none or Denagard/CTC, 35/400 g/ton) and Carnichrome (none, 25, and 100, or 50 and 100 ppm, respectively, of L-carnitine and chromium picolinate). No interactions between Carnichrome and Denagard/CTC were detected (P>0.17). Pigs fed Denagard/ CTC had improved ADG (P<0.01), and F/G (P<0.02) from d 0 to 10, 10 to 29, 0 to 29, and overall (d 0 to 43) compared with those of pigs fed diets without Denagard/CTC. In addition, pigs fed diets containing Denagard/CTC tended to have increased ADFI (P<0.08) from d 0 to 10, and significantly increased ADFI (P<0.01) from d 10 to 29, 0 to 29, and overall (d 0 to 43). No differences in ADG, ADFI, and F/G were seen for pigs fed diets containing either rate of Carnichrome, compared with those of pigs fed the negative control diet. For the period d 29 to 43, when pigs were fed a common phase 3 diet, there were no differences in ADG, ADFI, or F/G between treatments (P>0.14), and no carryover effect of medication resulted. Pigs fed nursery diets containing Carnichrome did not have enhanced growth performance, but pigs fed diets containing Denagard/CTC had improved ADG, ADFI, and F/G compared with those of pigs fed diets without Denagard/CTC.
Keywords: Swine; Antibiotics; L-carnitine; Chromium; Pigs; Weanling pigs